PATIENT SATISFACTION WITH MEDICAL ENCOUNTERS IN NEUROLOGY OUTPATIENT CLINICS. Issue 11 (14th October 2015) - Reuber, Markus; Toerien, Merran; Wiseman, Hannah; Shaw, Rebecca; Duncan, Rod
Abstract : Aim: Recent public policy documents have emphasised the need for healthcare practitioners to give patients choice. As part of a larger qualitative project investigating how neurologists give patients choices, we explored whether evidence of patient choice is associated with higher patient satisfaction. Method: Fourteen neurologists and 223 patients were recruited in neurology outpatient clinics in Glasgow and Sheffield. All participants completed post-appointment questionnaires assessing whether choice was offered or perceived. Clinicians also rated the extent to which symptoms were medically explained. Patients completed the Medical Interview Satisfaction Scale-21 (MISS-21). Results: Two dominant factors contributed to the total MISS-21 scale, 'rapport' and 'distress-relief'. Regression analysis showed that the extent to which symptoms were medically explained predicted most of the variance on both subscales and the total MISS-21 score. Spearman's rho correlations showed greater patient satisfaction if symptoms were medically explained and if no choice had been offered or perceived. Conclusion: There was no evidence that giving patients choices in interaction increased patient satisfaction with clinical encounters. Our findings suggest that patient satisfaction is most strongly influenced by the extent to which neurologists perceive symptoms as medically explained.